Proposed solutions on waste issues in Kulon Progo regency through society 5.0 community service - Anindyajati, Adhi (Jurnal Atma Inovasia, 2022)
Waste is a global environmental issue. The problem can be unique in each area and it can be organic or plastic. One of the solutions for waste problems is waste processing. In this article, community service on programs related to waste and environmental issues is presented. Due to covid-19 pandemic, community service was carried out with society 5.0 approach instead of with the traditional on-field. Waste problems in Kulon Progo regency were explored, particularly in Giripeni, Temon Wetan, Bendungan, and Kulwaru village. Through literature study, waste-related concerns in each village were explored, followed by the development of solution for each issue. Organic wastes could be processed into organic fertilizer and hand craft, while plastics could be an advantageous ingredient for making paving block. The outputs were arranged in educative and interesting ebooks for inspiring and encouraging positive activities for community empowerment.